The Influence of Job Characteristics, Competence, and Work Environment on Employee Performance at the Office of City Services and Spatial Planning of the Covalima Municipal Authority - Amaral, Damião (Jurnal Ar Ro'is Mandalika (Armada), 2025)
The influence of job characteristics, competencies and work environment on employee performance at the City Services and spatial planning office of the Covalima Municipal Authority. The research aims to determine the influence of job characteristics, competencies and work environment on employee performance at the City Services and Spatial Planning office of the Covalima Municipal authority. This research uses a path analysis model. The sample was 97 employees at city service offices. Data was obtained through distributing questionnaires via Google Form. The results of the analysis show that the β value for the job characteristics variable (X 1 ), competency (X 2 ), and work environment (X 3 ). This shows that the job characteristics (X 1 ) variable has the most dominant influence on employee performance (Y) at the City Services Department and Covalima Municipal Authority Spatial Planning because it has the largest β value.